The prevalence of burnout syndrome in medical students (Archives of Clinical Psychiatry, 2016)
Background Burnout syndrome (BS) is a set of psychological symptoms resulting from the interaction between chronic occupational stress and individual factors. These symptoms include emotional exhaustion, depersonalization and decreased professional satisfaction. BS is manifested in a variety of professions and is prevalent in contexts in which health professionals are required to interact directly with the public. Objective To determine the prevalence of BS among medical students at a university in Ceará State, Brazil. Methods Of the 517 students enrolled in their first to eighth semester in 2013, 376 (72.7%) were contacted. A socio-economic evaluation questionnaire and the Maslach Burnout Inventory – Human Services Survey (MBI-HSS) were administered. Statistical analysis was conducted using SPSS 20.0. Two groups – burnout/risk and non-burnout – were compared using the chi-square and likelihood ratio tests with a significance level of 5%. Variables with p < 0.20 were included in a multivariate analysis logistical regression model. Results Burnout was detected in 14.9% of the students, and 57.7% showed a risk of developing the syndrome. Logistic regressions showed an association between burnout and “have failed examinations” and “have considered abandoning the course”, p = 0.047 and p < 0.0001, respectively. Discussion Psychopedagogy should be implemented to address the high prevalence of burnout in medical students.